Bulk CO2/CH4 separation for offshore operating conditions using membrane process - Norwahyu Jusoh,; Kok, Keong Lau; Yin, Fong Yeong; Azmi M. Shariff, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The increasing demands of natural gas pushes energy industries to explore the reservoirs contain high CO2 concentration and impurities including heavy hydrocarbons. High efficiency of using membrane technology in CO2-natural gas separation has extended its potential application to offshore environment. Due to the limited studies related with the separation of CO2 under offshore conditions, the present work has investigated the separation performance of a commercial membrane in removing bulk CO2 from methane at elevated pressure condition. A wide range of offshore operating conditions including pressure from 10 to 50 bar, CO2 concentration from 25 to 70% and temperature of 30oC, 40oC and 50oC were studied. High relative CO2 permeance and relative CO2/CH4 selectivity were observed when the pressure and the CO2 concentration increased. This work, therefore substantial is to bridge the gap and facilitates the application of membrane technology for offshore operating conditions.